Generalized pustular psoriasis is a disease distinct from psoriasis vulgaris: evidence and expert opinion. (3rd October 2022) - Bachelez, Hervé; Barker, Jonathan; Burden, A. David; Navarini, Alexander A.; Krueger, James G.
ABSTRACT: Introduction: Generalized pustular psoriasis (GPP) is a rare, severe, clinically heterogeneous disease characterized by flares of widespread, noninfectious, macroscopically visible pustules that occur with or without systemic inflammation, and are associated with significant morbidity and mortality. Historically, GPP has been classified as a variant of psoriasis vulgaris (PV, or plaque psoriasis); however, accumulating evidence indicates that these are distinct conditions, requiring different treatment approaches. Areas covered: In this perspective article we review evidence that supports the classification of GPP as distinct from PV. Expert opinion: The histopathologic and clinical appearance of GPP is distinct from that of PV and fundamental differences exist between the two conditions in terms of genetic causes and expression-related mechanisms of disease development. GPP results from dysregulation of the innate immune system, with disruption of the interleukin (IL)-36 inflammatory pathway, induction of inflammatory keratinocyte responses, and recruitment of neutrophils. PV is driven by the adaptive immune system, with a key role played by IL-17. Considering GPP as a separate disease will enable greater focus on its specific pathogenesis and the needs of patients. Many treatments for PV have insufficient efficacy in GPP and a therapeutic approach developed specifically for GPP might lead to better patient outcomes. Plain Language Summary: Generalized pustular psoriasis (GPP) is a rare disease. During episodes of worsening disease, the immune system attacks the skin. This causes large areas of skin to become red and painful, pus-filled blisters suddenly form. Some people with GPP have a history of another, more common, skin condition called psoriasis vulgaris (PV). People with PV develop patches of scaly, itchy skin. In the past, GPP was classed as a type of PV and treated with the same medicines. However, these medicines do not work well in GPP. Researchers now understand more about what causes GPP and how it differs from PV. GPP can cause medical problems throughout the body, leading to life-threatening complications. This means that people with GPP often need urgent medical treatment in hospitals. People with PV are mostly treated outside of hospitals. Any other medical problems are not usually due to PV itself. Researchers have found several genes that are altered in people with GPP and PV, and they differ between the two diseases. For example, changes in a gene called IL36RN are common in GPP but are not seen in PV. The skin of people with these two diseases also looks different under a microscope. Knowing more about GPP and how it differs from PV will help people with GPP to be diagnosed more quickly. It will also help researchers to develop new medicines specifically for GPP, so people can receive better treatment in the future. Graphical Abtract: uf0001